Effects of childhood trauma on pain‐related distress in adults. (9th July 2021) - Walton, Dave Mark; Tremblay, Paul; Seo, Wonjin; Elliott, James Matthew; Ghodrati, Maryam; May, Curtis; MacDermid, Joy Christine
Abstract: Background: Much of the work in post‐musculoskeletal (MSK) trauma and distress has been conducted through frameworks that start from the injury and go forward to better understand the trajectories and predictors of recovery. However, stress–diatheses models suggest that reactions to trauma are shaped by pre‐existing experiences of the person more than the parameters of the event itself. In this study, we explore the effects of adverse childhood experiences (ACEs) on traumatic threat appraisal, distress and pain‐related functional interference in adulthood. Methods: Adult participants with acute, non‐catastrophic musculoskeletal trauma completed a battery of questionnaires that included the Adverse Childhood Experiences Questionnaire (ACEQ), the Brief Illness Perceptions Questionnaire (BIPQ), the Traumatic Injuries Distress Scale (TIDS) and the Brief Pain Inventory (BPI). An a priori model was evaluated through path analysis to determine the variance in BPI Interference scores explained through direct or indirect pathways between these variables (ACEQ‐>BIPQ, BIPQ‐>TIDS, TIDS‐>BPI). The analysis was repeated for the sample when disaggregated by sex. Results: In n  = 114, the base model was saturated. After removing non‐significant pathways, the ACEQ‐>BIPQ‐>TIDS‐>BPI paths were significant and in the expected direction, explaining 57.1% of variance in acute BPI Interference score. When disaggregated by sex, the effect of ACEs on threat appraisal was only significant in men and not women, although this analysis was exploratory. Conclusions: Acute pain‐related interference could be predicted by post‐traumatic distress and threat appraisal. Threat appraisal could be further predicted through ACEs, more childhood adversities were associated with more threatening appraisal of trauma in adulthood. The disaggregated finding that the effects of childhood adversities were only significant in males requires further exploration. Significance: This study explores the potential pathways of the stress–diathesis model while focusing on adverse childhood experiences as a novel contribution to the field of acute post‐trauma pain. The findings may inform future research design and interpretation of acute‐to‐chronic pain risk stratification tools.